Voices from the emergency department: A theoretical framework analysis on patient experiences of care in emergency departments of Newfoundland and Labrador, Canada - Aswathy Geetha Manukumar; Nahid Rahimipour Anaraki; Holly Etchegary; Anna Walsh; Oliver Hurley; Christopher Patey; Paul Norman; Shabnam Asghari (PLoS ONE, 2026)
Background Patient experience in the emergency department (ED) encompasses different aspects of care, such as respect, communication, timeliness, shared decision-making, and care transition. The inherently stressful ED environment presents additional challenges for providers in ensuring a positive patient experience. Studying patient experience allows health systems to recognize areas of care that need improvement and introduce strategies to improve patient-centred care. Objectives To explore the patient experience of emergency department care in Newfoundland and Labrador (NL), Canada. Methods This qualitative study collected data from patients who visited two urban and two rural EDs in NL via telephone surveys and semi-structured interviews. Five researchers used a theoretical framework, symbolic interactionism, to analyze open-ended survey responses and semi-structured interviews. Patient research partners were consulted to ensure the themes reflected their lived experiences. Results A total of 836 responses were analyzed (831 survey responses, five semi-structured interviews), leading to six key themes on patient experience. They are: (1) Mutual respect and trust in providers, (2) Timeliness of care, (3) Communication, (4) Comfort and accommodations, (5) Information sharing and decision-making, and (6) Continuity of care. Conclusion Our findings show an immediate need to improve the patient experience of ED care and highlight areas within these themes that could be targeted for improvement. We recommend regular training programs for healthcare providers to improve their interpersonal skills, the addition of patient navigators, and modifications to the triage system for vulnerable populations to improve patient experience and provide patient-centred care.